Rooting of Spiraea sorbifolia Linn. Stem Cuttings - Chandra, J. P.; Khushdil, M. M. (Indian Forester, 1977)
Spiraea sorbifolia Linn. is useful species for soil conservation, fodder, fuel and regeneration of Chilgoza in cold deserts of Himachal Pradesh. The species can be easily multiplied by hard wood stem cuttings. In study under report, 52 percent of cuttings rooted without any aid of root promoting hormone and irrigation.